CHI AND MORAL AUTONOMY IN IGBO THOUGHT SYSTEM (2014)
Chi, in Igbo traditional thought, is conceived of as a being responsible for the individuals success and failure, in which the persons ontological moral autonomy is denied. Existing studies have addressed the idea of Chi from Christian and literary perspectives, which emphasise fatalistic interpretation, but have not adequately studied the concept in relation to the individual as an autonomous moral agent. This study, therefore, investigated the concept Chi in Igbo culture, with a view to identifying the moral and ontological roles and attributes of Chi, in which the individual enjoys autonomy. The study adopted as its framework, Kants theory on moral autonomy, which holds that the will of a rational being is not subject to moral principles. Six relevant texts in metaphysics, eight texts in ethics and six texts on Igbo culture/African philosophy were purposively selected because they addressed the issues of Chi, moral autonomy and Igbo philosophy. The methods of conceptual-analysis and reconstruction were adopted. The former was used in the interrogation of relevant texts and positions, and to clarify the key concepts such as Chi, freedom, responsibilityand moral autonomy, while the latter was employed to reconcile the conception of Chi as different from the individual, and yet decides the individuals wellbeing. Texts in metaphysics establish that the human persons are not in control of their well being, but do not consider the human will in its ontological dimension as very significant in their explanations, and therefore, under-explore the connection between the existence of destiny and the state of the human will. Texts in ethics reveal that the individual is bound to behave in certain laid down ways in which the individual does not enjoy autonomy, but is held responsible for their actions. These positions do not explicitly incorporate the human will, as the initiator and driver of decisions and actions in human persons. Texts in Igbo philosophy reveal that, ontologically, the (self) onwe in Igbo culture is empirical and enjoys moral autonomy. There are Igbo proverbs that affirm the idea of moral autonomy, freedom and responsibility in Igbo culture. For instance, Arusi/ agbarakpamngaga, egosiyaosisiejirimeputaya- a god cannot be more powerful than the owner, else, it will be told of what wood it is made from, emphasises human freedom and responsibility. Critical reflection on the idea of Chi demonstrates that the human person is morally autonomous and that the human will is not bound by any external forces, because every individual has akonauchewhich decides moral actions as being right or wrong. For instance; iheonyemetara, ya-buru- whatever individuals do, they alone bear the consequences, emphasises moral autonomy. The idea of Chi in Igbo culture demonstrates that the human person, as a moral agent, is morally autonomous. Therefore, the concept Chi plays both moral and ontological roles in the individuals action which makes it (Chi) not to be conceived as fatalistic or deterministic since the individual enjoys some freedom and takes responsibility for their actions.